2006
DOI: 10.1111/j.1464-410x.2006.06060.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes in elective partial vs radical nephrectomy for clear cell renal cell carcinoma of 4–7 cm

Abstract: RESULTSIn the PN and RN cohorts the treatment failed in one and 20 patients, respectively; the median follow-up was 21 months. The hazard ratio (95% confidence interval) for PN after adjusting for disease severity was 0.36 (0.05-2.82; P = 0.3). Using planned PN as a predictor (intent-to-treat analysis) the hazard ratio was 1.06 (0.32-3.53; P = 0.9). In the propensity-score model, planned PN was associated with a hazard ratio of 1.75 (0.50-6.14; P = 0.4). The serum creatinine level 3 months after surgery was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
1
10

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(123 citation statements)
references
References 24 publications
3
109
1
10
Order By: Relevance
“…Patients with only one postoperative GFR estimation (49 partial nephrectomy, 27 radical nephrectomy) were censored at the time of that GFR estimation. 3-year and 5-year probabilities of freedom from new onset of GFR lower than 60 mL/min per 1·73 m 2 were 80% (95% CI 73-85) and 67% (57-75), respectively, for patients who underwent partial nephrectomy, compared with corresponding values of 35% (28-43) and 23% (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) for those who underwent radical nephrectomy (p<0·0001; figure 2). Median time to development of GFR lower than 60 mL/min per 1·73 m 2 was 18 months (IQR 10-55) for the radical nephrectomy group and was not reached for the partial nephrectomy group.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with only one postoperative GFR estimation (49 partial nephrectomy, 27 radical nephrectomy) were censored at the time of that GFR estimation. 3-year and 5-year probabilities of freedom from new onset of GFR lower than 60 mL/min per 1·73 m 2 were 80% (95% CI 73-85) and 67% (57-75), respectively, for patients who underwent partial nephrectomy, compared with corresponding values of 35% (28-43) and 23% (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) for those who underwent radical nephrectomy (p<0·0001; figure 2). Median time to development of GFR lower than 60 mL/min per 1·73 m 2 was 18 months (IQR 10-55) for the radical nephrectomy group and was not reached for the partial nephrectomy group.…”
Section: Resultsmentioning
confidence: 99%
“…Partial nephrectomy has wellestablished oncologic outcomes data comparable to radical nephrectomy, 14,[17][18][19] which can lead to an increased risk of chronic kidney disease 20,21 that is associated with increased risks of cardiovascular morbidity and mortality, according to population-based studies. Compared with radical nephrectomy, partial nephrectomy can preserve renal function, decrease overall mortality, and reduce frequency of cardiovascular events.…”
Section: Treatment Of Localized Diseasementioning
confidence: 99%
“…(Becker et al, 2006b;Huang et al, 2006;Patard et al, 2004;Thompson et al, 2005) In addition to the benefits of preserving renal function and preventing cardiovascular complications, topics discussed in detail in the ensuing sections, evidence strongly supports the notion that cancer control and risk of cancer-related death are not compromised when a partial nephrectomy is performed instead of a radical procedure. (Dash et al, 2006;Leibovich et al, 2004) Although data from the National Cancer Institute SEER program demonstrated that partial nephrectomy was underutilized at the beginning of this century (2000)(2001)(2002), with only 20% of patients with tumors 2-4cm in size receiving this procedure, these rates are changing in favour of a nephron-sparing approach. Miller et al, 2006) In fact, a retrospective review of 1,533 patients treated with partial or radical nephrectomy between 2000-2007 at Memorial Sloan Kettering Cancer Center reported that nephron-sparing surgery was performed in approximately 90% of patients with T1a tumors.…”
Section: Renal Cortical Tumors: Heterogeneous Presentations and Oncolmentioning
confidence: 99%